The role of cryptotephra in refining the chronology of Late Pleistocene human evolution and cultural change in North Africa. (15th June 2015) - Barton, R.N.E.; Lane, C.S.; Albert, P.G.; White, D.; Collcutt, S.N.; Bouzouggar, A.; Ditchfield, P.; Farr, L.; Oh, A.; Ottolini, L.; Smith, V.C.; Van Peer, P.; et al.
Abstract: Sites in North Africa hold key information for dating the presence of Homo sapiens and the distribution of Middle Stone Age (MSA), Middle Palaeolithic (MP) and Later Stone Age (LSA) cultural activity in the Late Pleistocene. Here we present new and review recently published tephrochronological evidence for five cave sites in North Africa with long MSA/MP and LSA cultural sequences. Four tephra horizons have been identified at the Haua Fteah (Cyrenaica, Libya). They include cryptotephra evidence for the Campanian Ignimbrite (CI) eruption dating to ∼39 ka that allows correlation with other Palaeolithic sequences in the eastern Mediterranean and as far north as Russia. Cryptotephra have also been recorded from the Moroccan sites of Taforalt, Rhafas and Dar es-Soltane 1. At Taforalt the geochemical composition suggests a provenance in the Azores, while examples from Sodmein (Egypt) appear to derive from central Anatolia and another unknown source. In these latter examples chemical compositional data from relevant proximal volcanic centres is currently lacking so the identification of tephra in layers of known age and cultural association provides the first reliable age determinations for distal volcanic events and their geographical extent. The future potential for tephrochronological research in North Africa is also discussed. Highlights: 5 sites in N Africa have crypotephra associated with Late Pleistocene archaeology. Tephra from Italian volcanic centres dates archaeological layers in Libyan sites. Long distance cryptotephras are recorded in Moroccan and Egyptian caves.